GEERTZ’S TRICHOTOMY OF ABANGAN, SANTRI, AND PRIYAYI: Controversy and Continuity (JOURNAL OF INDONESIAN ISLAM, 2017)
With the Presidential Decree on Hari Santri Nasional (National Santri Day) in 2015, the debate on Clifford Geertz’ trichotomy of santri-priyayi-abangan reemerges in Indonesian society. This article, first, intends to delineate the meaning of the trichotomy. Second, it summarizes three main critiques of the trichotomy, namely: 1) priyayi is more appropriately included in the category of social class, not religious category; 2) as social identity, abangan was not the term generally accepted by people in that category; 3) the category is not rigid and, in term of religiosity, most of Javanese people were actually in the grey area between santri and abangan. This article then shows that even though the trichotomy has drawn criticism from scholars, it has been accepted as a standard categorization of Indonesian society. The application of this trichotomy was not limited in the study of religion or anthropology, but it has been used in history, politics, economy, and military studies. The new challenges of this concept, i.e. the inclusion of social class or Marxist perspective in studying Java and the divergent of santri in contemporary time, which contributes to the reemergence of the trichotomy with a new spectrum is the last focus of this article.